Schistosome cercariae as the causative agent of swimmer's itch in Iceland - Kolárová, L; Skirnisson, K; Horák, P (Journal of helminthology, 1999)
During late summer in 1995 to 1997, repeated outbreaks of maculopapular skin eruptions were noted on the legs of children after wading in the pond in the Family Park in Laugardalur, Reykjavík, Iceland. Clinical symptoms developing on the legs resembled those of cercarial dermatitis. An examination of Lymnaea peregra snails from this pond and from the adjacent Lake Tjornin resulted in detection of previously undescribed schistosome cercariae. This is the first report of schistosomes in Iceland and also the most northern occurrence of these parasites in Europe.
Keywords: dermatitida; Schistosomiasis; Island; Iceland; Child; dítě; Dermatitis; Pruritus; Lymnaea; Mice, Inbred ICR; Schistosoma; schistosomóza; plavání; Animals; Swimming; lidé; Humans; pruritus; zvířata; parazitární onemocnění kůže; Skin Diseases, Parasitic; myši; myši inbrední ICR; Mice